Manajemen Konflik - Wardana, Adi Kusuma; Aulia, Muhammad Fajrur Rizki; Suharyat, Yayat (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
Conflict in the world of education is an unavoidable phenomenon and can have a significant impact on learning success. Therefore, conflict management is a critical aspect in creating a positive and effective learning environment. This research discusses the sources of conflict as well as the basic concepts of conflict management and applies them in an educational context. This research uses a library method by collecting sources from journals and scientific papers. One solution that is quite efficient for increasing productivity in educational institutions is to manage conflict. The ability of educational institution leaders to handle conflict well depends on their ability to combine various existing approaches, such as validating incoming news, discussions, negotiations, looking for mediators (judges), making peace, and others. Therefore, to ensure that efforts to improve the quality of work continue to be implemented optimally, leaders of educational institutions should always strive to continue to improve their skills, knowledge and innovation in managing conflict.